Absorption and Theatricality in the Staging of Contempt: Flaubert, Baudelaire, Huysmans - ZANETTA, Julien (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
Drawing on two categories suggested by art historian Michael Fried – absorption and theatricality –, this article suggest a specification relative to how we feel and express a particular emotion: contempt. To better understand the distinction between absorbed and distanced contempt, and all the emotional consequences that ensue, three specific and contrasting examples taken from Flaubert, Baudelaire and Huysmans are analysed here.